2009
DOI: 10.2478/v10046-010-0002-0
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of firefighters-rescuers' work severity in relation with interaction between physical and mental load

Abstract: Assessment of firefighters-rescuers' work severity in relation with interaction between physical and mental load The present work is focused on occupational health problems caused by ergonomic risk in firefighting, which is one of the most hazardous occupations. The aim was to evaluate the work heaviness degree and to estimate the muscle fatigue for a study group consisting of 12 firefighters-rescuers. Applying qualitative ergonomic analyses (OWAS a.o.) and clinical experiments to determine consumed me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…In this study, there was no significant association between educational level and age with mental load score, but in the study by Young et al, mental load score was significantly related to age differences and older workers were more vulnerable to mental load compared to younger workers (19). Roja et al conducted a study aiming at evaluating mental and physical load of firefighters and found that physical load had the highest value and total mental workload based on NASA questionnaire was 58 and 65 in two groups of firefighters and commanding officers respectively (20). Overall considering contradiction in different studies two conclusions can be achieved.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, there was no significant association between educational level and age with mental load score, but in the study by Young et al, mental load score was significantly related to age differences and older workers were more vulnerable to mental load compared to younger workers (19). Roja et al conducted a study aiming at evaluating mental and physical load of firefighters and found that physical load had the highest value and total mental workload based on NASA questionnaire was 58 and 65 in two groups of firefighters and commanding officers respectively (20). Overall considering contradiction in different studies two conclusions can be achieved.…”
Section: Discussionmentioning
confidence: 99%
“…This issue is considered in the assessment of one's capacity for work, as mental load influences physical load (ROJA et al, 2009). It is important to note that physical effort, as previously mentioned, is very intense in agricultural work, since planting, harvesting, and preparing the soil, is mainly performed using simple and manual tools (e.g., shovel, hoe), which do not minimize physical effort, but rather increase it.…”
Section: Discussionmentioning
confidence: 99%
“…According to past research, some hazards will cause musculoskeletal disorders and psychological health problems among firefighters, like the psychological demands toward the firefighters promoted to unergonomic working postures in firefighters (Roja et al, 2009). Soteriades et al (2019) investigated the relationship between occupational stress and musculoskeletal symptoms in Cyprus Fire Service and found that 11% of the firefighters were facing moderate to extremely severe stress, and 40% of the firefighters facing musculoskeletal disorders, back pain was the highest.…”
Section: Research Papermentioning
confidence: 99%